(untitled) (Emancipação, 2025)
This article has in view to introduce a reflection about the Social Worker professional practice, recognizing dimensions, in order to situate the Social Work instrumentality and the technical-operation that the professionals use. After, will be introduced, succinctly, some principal tools used for the Social Workers in their professional practice, and also some final considerations.